DOI: 10.1007/978-0-387-09768-8_8
|View full text |Cite
|
Sign up to set email alerts
|

The Service Behind the Service: Sensegiving in the Service Economy

Abstract: In this modest essay, we reflect on the crucial role of sensegiving, and hence sensemaking, in the creation of IT-enabled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Interaction and relations between the service worlds are therefore increasingly important in order to understand the efficiency and quality of service [6]. Service platforms such as social media are an important aspect of service not only for enabling scale, scope and reach of resources (skills and knowledge) [16,30] but also because they are an important part of the shaping of the design, delivery and influence of service [14,31].…”
Section: Notions Of Servicementioning
confidence: 99%
“…Interaction and relations between the service worlds are therefore increasingly important in order to understand the efficiency and quality of service [6]. Service platforms such as social media are an important aspect of service not only for enabling scale, scope and reach of resources (skills and knowledge) [16,30] but also because they are an important part of the shaping of the design, delivery and influence of service [14,31].…”
Section: Notions Of Servicementioning
confidence: 99%
“…Chandler and Vargo (2011) emphasize the influence of context on value co-creation in services, while Ramiller and Chiasson (2008) suggest moving from discrete models of service to the notion of an "organizing vision" encompassing multiple contextually relevant discourses -regulatory, governmental, ethical as well as commercial, technological and entrepreneurial. They suggest that understanding broader organizing visions (2008, p. 15): … helps define how people and their organizations think substantively about the possibilities while also lending normative force to the service innovation.…”
Section: Calling Out the Materiality Of Servicesmentioning
confidence: 99%
“…Working across such boundaries -in effect, engaging with different "service worlds" (Bryson et al 2004;Barrett and Davidson 2008) -has heightened awareness that the ways in which service interactions, relationships, and encounters are structured matters (Gutek et al 2000). As information systems become more central to the structuring of services, there is growing recognition that technology not only increases their scale, scope, and reach, but also shapes their design, delivery, and influence (Ramiller and Chiasson 2008). Rouse and Baba (2006, p. 69) note that accounts of work may be constructed from many different perspectives, each of which holds its own distinct value and each of which cuts the world in its own way:…”
Section: Introductionmentioning
confidence: 99%
“…In the context of knowing, appropriation refers to contemporary practices of adapting information technologies like search engines in different types of unanticipated uses rather than utilising them merely for their asserted purposes (Huvila, 2012). Even if there are many limiting factors that are (either tangible or abstract) similarly unavoidable, SST scholarship has convincingly shown that in addition to inescapable constraints technologies and ideas are made to do things by their users (Ramiller and Chiasson, 2008;Twidale et al, 2008). Technologies and other 'things', including knowledge (e.g.…”
Section: This Is How It Is!mentioning
confidence: 99%